PERAN STRES KERJA DALAM MEMEDIASI PENGARUH WORK-LIFE BALANCE DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN GIANYAR - Ni Wayan Sri Pradnyani; Agoes Ganesha Rahyuda (Jurnal Ilmu Manajemen, 2022)
This study aims to analyze the role of job stress in mediating the effect of work-life balance and competence on the performance of Dispersip Gianyar employees. The research location is in Dispersip of Gianyar Regency with 59 employees, but the sample used is only 54 people due to incomplete answers. Data was collected using a survey approach, and the instrument of this research was a questionnaire which was measured using a Likert scale. Data analysis was carried out using PLS-based SEM, namely Smart Pls 3. The result of this research shows that work-life balance and competence had a positive and significant effect on performance but had a negative and significant effect on job stress, while job stress had a negative and significant effect on performance. Job stress partially mediates the relationship between work-life balance and competence on performance. The implications of this research theoretically support the findings of previous studies as well as studies related to attribution theory. The practical implication for the Dispersip of Gianyar Regency is to be able to maintain performance by supporting work-life balance, providing training to increase competence, and trying to reduce work pressure on employees. For further researchers, they can conduct research by considering demographics as a variable that affects performance.